Open Access Initiative – why, and are we willing to try? - Salvesen, Helge (Ravnetrykk, 2020)
In the very early days of the Open Access movement (the concept had, in fact, just been coined at that time) former library director at UiT Helge Salvesen held the introductory speech at a seminar called "Open Online Access to Research", organised by the Norwegian Council for Higher Education, in Oslo, November 2003. In his speech, Salvesen describes the forms of Open Access now known as Gold OA and Green OA, emphasising the need for institutional repositories and other kinds of infrastructure to facilitate openness and transparency in research.